(untitled) (Veterinary Science, 2017)
An investigation of the cause of intersexuality in an egg’s producer commercial company of White Leghom hens line was carried out. The birds were one year old and were in laying phase. Approximately 11% of the flock presented cases of intersexuality evidenced by phenotypical and conduct changes. To explain the above phenomenon, the possibility of an infectious (Marek, Leucosis or Infectious Bronchitis). These hipothesis were rejected following a serological and histopathological study. Morphological study revealed differing degrees of left ovarian and oviductal atrophy with a paral1el development of right gonadal tissues similar to testes and in sorne cases development of left ovotestes. The right and left gonads of the intersexes presented irregular distribution of seminiferous tubules, with spermatogenic epithelium in différént phases. However, a significant part of the tubules presented few spermatogonia and incomplete spermiogenesis. In the left ovotestes the fol1icular configuration was absent, except for a few atresic follicles in the cortex. The karyotype was researched from peripherallymphocytes establishing the presence of ZZW, apparent causative agent ofthe problem. High incidence ofhermaphrodism and the presence ofZZW sex chromosomes lead us to believe that a high degree of inbreeding or other breeding strategies might have predisposed the appearing oftriploid chromosomes